DISAIN PAYUNG OTOMATIS PENDETEKSI CUACA HUJAN DAN CUACA PANAS BERBASIS MICROCONTROLER BAGI LANSIA - Elliarini isabela; M. Yusuf Sanny (POLITEKNIK PIKSI GANESHA, 2019)
The current weather conditions are uncertain often make us overwhelmed when it rains arrive, especially when we are in an open area like a residential field. In other conditions when carrying out their daily prayer on an open area often make worshipers became alarmed because of his fear of sudden rain. Therefore they invented an automated tool control system to condition the area of rain that came suddenly. In this tool there is water control sensors with microcontroller ATMega8 required as a data processor and a motor driver where the driver will set the DC motor rotation (right or left) to the movement of the umbrella. Conditions required by the umbrella is when the motor rotate to the right and then the umbrella will open when the motor rotate to the left then the umbrella will close again.